A agência humana do professor de inglês no desenvolvimento de saber glocal na perspectiva sócio-histórica e dialética - Santos, Fátima Aparecida Cezarim dos [UNESP] (2014)
This work is grounded on the qualitative paradigm, elaborated through an interpretative research with a sociocultural focus. This research aims to interpret and discuss the agency of an English language teacher in the development of local knowledge, who has taught in two full time municipal schools located in low income communities, in a city of the São Paulo State. The comprehension of the agentive exercise and the local knowledge construction has required starting from the teaching praxis of the participant, searching for identifying her knowledge-base, her English teaching methodologies and her agentive attitude for the construction of local knowledge in the teaching practice. Besides, the attitude of the teacher before English language local necessities and its developments were investigated. The data generation procedures followed the ethnographic basis. This study is oriented by the historical dialectical materialism method and the technique for the data treatment is the content analysis. As a result, data interpretation has showed that the participant prioritized the usage of a global knowledge, without generating a local knowledge which means a rupture with the global knowledge, as it is preached by specialized literature. Nevertheless, the teacher's practice was all pervaded by a mediated human agency exercise in the interrelation between the human, material and institutional constitutive elements in her teaching action context. Such elements can only be understood in the historical, social, political, economic dynamics, where the teacher's action took place: in the concrete and singular experience of teaching education and of professional practice with its contradictory elements. Last but not least, the present research shows the lack of formal and practical knowledge about the notion of development of local knowledge in the education and in the teaching action of an English teacher which, probably, can also be in other...